Organoleptic Test of Green Mustard Leaf Flour (Brassica juncea) Due to Various Types of Preliminary Treatments - Dyah Ayu Setyawati; Ida Agustini Saidi (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of preliminary treatment on the quality of organoleptic green mustard leaf flour.This research was conducted in the Laboratory of prodak development of Muhammadiyah University sidoarjo from February to April 2020 using descriptive methods. The experiment was compiled in a Complete Randomized Design with variations of preliminary treatment conducted ie without blanching (TPP), water blanching (PPR), water blanching with soaking salt solution 1% (PPRG 1), water blanching with soaking salt solution 2% (PPRG 2), water blansing by immersion of 0.1% na metabisulfite solution ((PPRN 1), water blanching by immersion of 0.2% na metabisulfite solution (PPRN 2), steam blanching (PPK) and microwave blanching (PPM). Based on organoleptic tests showed that the preliminary treatment had a noticeable different effect on color and aroma.The best treatment in the manufacture of mustard flour hijua with preliminary treatment is steam blansing that gives a normal value of 0.98 with organoleptic characteristics of color 6.04 (likes-very likes) and organoleptic aromas of 6.12 (likes-very likes).